Some novel hybrid quinazoline-based heterocycles as potent cytotoxic agents - Mahla Malekzadeh; Shadi Dadkhah; Ghadam Ali Khodarahmi; Parvin Asadi; Farshid Hassanzadeh; Mahboubeh Rostami (Wolters Kluwer Medknow Publications, 2022)
Background and purpose: In this study, some new cytotoxic hybrid structures were synthesized by combining pyrazolinone and imidazolinone rings with quinazoline pharmacophores. Experimental approach: The benzoxazinone, pyrazolo-quinazoline fused ring, and imidazolinone anchored quinazoline derivatives were synthesized by simple ring-opening, ring expansion, and ring closure strategies from oxazolones. The molecular docking studies of the final derivatives were accomplished on the epidermal growth factor receptor enzyme. The cytotoxic effect of the final compounds on the MCF-7 cell line was evaluated by MTT assay. Findings/Results: The docking results confirmed the optimized electrostatic, H-bonding, and hydrophobic interactions of structures with the key residues of the active site (ΔGbin < -9Kcal/mol). The derivatives have been obtained in good yield and purity, and their structures were confirmed by different methods (FT-IR, 1H-NMR, 13C-NMR, and CHNS analysis). The IC50s of all final derivatives against the MCF-7 cell line were lower than 10 μM, and between all, the IXa from pyrazolo-quinazolinone class (IC50: 6.43 μM) with chlorine substitute was the most potent. Furthermore, all derivatives showed negligible cytotoxicity on HUVEC normal cell line which would be a great achievement for a novel cytotoxic agent. Conclusion and implications: Based on the obtained results, pyrazolo[1,5-c] quinazolin-2-one series were more cytotoxic than imidazolinone methyl quinazoline-4(3H)-ones against MCF-7 cells. Chlorine substitute in the para position of the aromatic ring improved the cytotoxicity effect in both classes. It could be related to the polarizability of a chlorine atom and making better intermolecular interactions. Further pre-clinical evaluations are required for the promising synthesized cytotoxic compounds.